Đang tải thanh công cụ tìm kiếm ...
Phép Tính Online

Tính:

Tính

a) \(4(cos{24^0} + \cos {48^0} - \cos {84^0} - \cos {12^0})\)

b) \(96\sqrt 3 \sin {\pi  \over {48}}\cos {\pi  \over {48}}\cos {\pi  \over {24}}\cos {\pi  \over {12}}\cos {\pi  \over 6}\)

c) \(\tan {9^0} - \tan {63^0} + \tan {81^0} - \tan {27^0}\)

Trả lời:

a)

\(\eqalign{
& cos{24^0} + \cos {48^0} = \cos ({36^0} - {12^0}) + \cos ({36^0} + {12^0}) \cr
& = 2\cos {36^0}\cos {12^0} \cr
& \cos {84^0} + \cos {12^0} = 2\cos {36^0}\cos {48^0} \cr
& 4(\cos {24^0} + \cos {48^0} - \cos {84^0} - \cos {12^0}) = 8\cos {36^0}(\cos {12^0} - \cos {48^0}) \cr
& = 8\cos {36^0}.2\sin {30^0}.\sin {18^0} = 8\cos {36^0}\sin {18^0} \cr
& = 8\cos {36^0}.\sqrt {{{1 - \cos {{36}^0}} \over 2}} \cr} \)

Đặt 360 = x ta có:

\(\eqalign{
& sin3x{\rm{ }} = {\rm{ }}sin{\rm{ }}\left( {{{180}^0} - 3x} \right) = sin2x \cr
& \Leftrightarrow 3\sin x - 4{\sin ^3}x = 2\sin x\cos x \cr
& \Leftrightarrow 3 - 4(1 - {\cos ^2}x) = 2{\mathop{\rm cosx}\nolimits} \cr
& \Leftrightarrow 4co{s^2}x - 2\cos x - 1 = 0 \cr
& \Rightarrow {\mathop{\rm cosx}\nolimits} = \cos {36^0} = {{1 + \sqrt 5 } \over 4} \cr} \)

Vậy :

\(4(cos{24^0} + \cos {48^0} - \cos {84^0} - \cos {12^0}) = 2(1 + \sqrt 5 )\sqrt {{{3 - \sqrt 5 } \over 8}}  = 2\)

b) 

\(\eqalign{
& 96\sqrt 3 \sin {\pi \over {48}}\cos {\pi \over {48}}\cos {\pi \over {24}}\cos {\pi \over {12}}\cos {\pi \over 6} \cr
& = 48\sqrt 3 \sin {\pi \over {24}}\cos {\pi \over {24}}\cos {\pi \over {12}}\cos {\pi \over 6} \cr
& = 24\sqrt 3 \sin {\pi \over {12}}\cos {\pi \over {12}}\cos {\pi \over 6} \cr
& = 12\sqrt 3 \sin {\pi \over 6}\cos {\pi \over 6} = 6\sqrt 3 \sin {\pi \over 3} = 9 \cr} \)                                                                             

c)

\(\eqalign{
& \tan {9^0} - \tan {63^0} + \tan {81^0} - \tan {27^0} \cr
& = {{\cos {{81}^0}} \over {\sin {{81}^0}}} + {{\sin {{81}^0}} \over {\cos {{81}^0}}} - ({{\cos {{27}^0}} \over {\sin {{27}^0}}} + {{\sin {{27}^0}} \over {\cos {{27}^0}}}) \cr
& = {1 \over {\sin {{81}^0}.cos{{81}^0}}} - {1 \over {\sin {{27}^0}.cos{{27}^0}}} \cr
& = {2 \over {\sin {{18}^0}}} - {2 \over {\sin {{54}^0}}} = {2 \over {\cos {{72}^0}}} - {2 \over {\cos {{36}^0}}} \cr
& = {2 \over {2{{\cos }^2}{{36}^0} - 1}} - {2 \over {\cos {{36}^0}}} \cr} \)

Thay  \(\cos {36^0} = {{1 + \sqrt 5 } \over 4}\) ta được: \(\tan {9^0} - \tan {63^0} + \tan {81^0} - \tan {27^0} = 4\)